1974
DOI: 10.1007/bf00421411
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitory effect of tolbutamide and glibenclamide (glyburide) on the pancreatic islets of normal animals

Abstract: Summary. Tolbutamide and glibenelamide (glyburide) were administered to normal hamsters, mice or rats in daily doses proportional to their body weight and equivalent to those used in human therapy. The animals were sacrificed after 6 to 8 weeks of treatment. Pieces of pancreas or isolated pancreatic islets were incubated or perifused in a medium containing glucose or tolbutamide, with or without leueine-114C or glucose-U-14C. The results indicate that the B cells of sulfonylurea treated animals synthesized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 38 publications
(30 reference statements)
5
32
0
Order By: Relevance
“…There is no evident reason to believe that the mechanism by which tolbutamide acutely stimulates insulin release in vivo is different from that proposed above. It is less certain whether the present demonstration of a delayed inhibition of insulin release by tolbutamide provides the sole explanation for the surprising decreased responsiveness of the islets after long-term treatment of animals with sulphonylureas [13][14][15].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…There is no evident reason to believe that the mechanism by which tolbutamide acutely stimulates insulin release in vivo is different from that proposed above. It is less certain whether the present demonstration of a delayed inhibition of insulin release by tolbutamide provides the sole explanation for the surprising decreased responsiveness of the islets after long-term treatment of animals with sulphonylureas [13][14][15].…”
Section: Discussionmentioning
confidence: 62%
“…Many clinical investigations have failed, however, to show a correlation between the lowering of blood glucose and an increase in plasma insulin levels after chronic treatment with sulphonylureas [9][10][11]. These latter observations have been related to unexplained reports showing that after long-term treatment of animals with sulphonylureas, the in vivo and in vitro insulin response to glucose was reduced [12][13][14][15].The present study carried out with isolated rat islets, was designed to explore in detail the mechanisms underlying the secretory and related ionic changes produced in B cells by tolbutamide. …”
mentioning
confidence: 99%
“…Desensitization by sulfonylureas. Approximately 30 years ago a reversible impairment of insulin secretion by sulfonylureas, such as tolbutamide or glibenclamide, was noted (36). The sulfonylurea-induced desensitization was described to be selective for sulfonylureas (37,38), but in vitro experimentation showed that exposure of islets to sulfonylureas also markedly reduced glucose-induced insulin secretion (39 -41).…”
Section: Desensitization By Depolarizing Insulin Secretagoguesmentioning
confidence: 99%
“…On the other hand, drugs such as sulfonylureas (the use of which in diabetes is currently under question [19]) have been postulated to act on insulin release through the cAMP system (20)(21)(22). The effect of these drugs on insulin production is a matter of controversy because they have been reported to stimulate (23) or to inhibit (24)(25)(26)(27) proinsulin biosynthesis in isolated islets of adult rodents.…”
Section: Introductionmentioning
confidence: 99%